Empirical Analysis of the Impact of Social Activity Participation on College Students’ Online Game Addiction: Investigating the Behavioral Patterns and Psychological Motivations of Chinese College Students - Dong, Yuanming (International Journal of Social Sciences and Public Administration, 2024)
This study explored the impact of social activity participation on online game addiction among Chinese college students, aiming to fill the gap in existing research on the lack of attention paid to social activities. Through a questionnaire survey, relevant data from 500 college students were collected, and the impact of social activity type, frequency and duration on online game addiction was analyzed. The study found that students who frequently participated in social activities were less likely to become addicted to online games, especially those who participated in sports activities and community service, whose addiction level was significantly lower than that of students who participated in online social activities. Psychological motivations such as escapism, gaining a sense of accomplishment and satisfying social needs play an important mediating role between social activities and online game addiction. The results show that increasing participation in offline social activities can help reduce online game addiction. The empirical analysis of this article provides empirical evidence for colleges and education departments to formulate intervention measures. It is recommended to encourage college students to participate in various social activities, especially sports and community service activities, to promote their mental health and social skills, form healthy gaming habits and effective time management strategies. Future research should further explore the specific impact of different types of social activities and verify the actual effect of intervention measures.